Cytochrome P450 monooxygenase-mediated tailoring of triterpenoids and steroids in plants - Malhotra, Karan; Franke, Jakob (Beilstein Journal of Organic Chemistry, 2022)
The cytochrome P450 monooxygenase (CYP) superfamily comprises hemethiolate enzymes that perform remarkable regio- and stereospecific oxidative chemistry. As such, CYPs are key agents for the structural and functional tailoring of triterpenoids, one of the largest classes of plant natural products with widespread applications in pharmaceuticals, food, cosmetics, and agricultural industries. In this review, we provide a full overview of 149 functionally characterised CYPs involved in the biosynthesis of triterpenoids and steroids in primary as well as in specialised metabolism. We describe the phylogenetic distribution of triterpenoid- and steroid-modifying CYPs across the plant CYPome, present a structure-based summary of their reactions, and highlight recent examples of particular interest to the field. Our review therefore provides a comprehensive up-to-date picture of CYPs involved in the biosynthesis of triterpenoids and steroids in plants as a starting point for future research.
Keywords: biosynthesis; CYPs; cytochrome P450 monooxygenases; plants; steroid; sterol; triterpene; triterpenoid

(untitled) - Qi, X.; Bakht, S.; Qin, B.; Leggett, M.; Hemmings, A.; Mellon, F.; Eagles, J.; Werck-Reichhart, D.; Schaller, H.; Lesot, A.; Melton, R.; Osbourn, A. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Kitagawa, I. (Pure Appl. Chem., 2002)

(untitled) - Zhang, M.; Sun, X.; Ren, R.; Su, L.; Xu, M.; Zheng, L.; Li, H. (Phytochem. Lett., 2022)

(untitled) - Xiong, J.; Kashiwada, Y.; Chen, C.-H.; Qian, K.; Morris-Natschke, S. L.; Lee, K.-H.; Takaishi, Y. (Bioorg. Med. Chem., 2010)

(untitled) - Thimmappa, R.; Geisler, K.; Louveau, T.; O'Maille, P.; Osbourn, A. (Annu. Rev. Plant Biol., 2014)

(untitled) - Nelson, D.; Werck-Reichhart, D. (Plant J., 2011)

(untitled) - Ghosh, S. (Front. Plant Sci., 2017)

(untitled) - Nguyen, T.-D.; Dang, T.-T. T. (Front. Plant Sci., 2021)

(untitled) - Bathe, U.; Tissier, A. (Phytochemistry, 2019)

(untitled) - Zhang, Y.; Ma, L.; Su, P.; Huang, L.; Gao, W. (Crit. Rev. Biotechnol., 2021)

(untitled) - Mizutani, M.; Sato, F. (Arch. Biochem. Biophys., 2011)

(untitled) - Miettinen, K.; Iñigo, S.; Kreft, L.; Pollier, J.; De Bo, C.; Botzki, A.; Coppens, F.; Bak, S.; Goossens, A. (Nucleic Acids Res., 2018)

(untitled) - Shang, Y.; Huang, S. (Plant J., 2019)

(untitled) - Bak, S.; Beisson, F.; Bishop, G.; Hamberger, B.; Höfer, R.; Paquette, S.; Werck-Reichhart, D. (Arabidopsis Book, 2011)

(untitled) - Hansen, C. C.; Nelson, D. R.; Møller, B. L.; Werck-Reichhart, D. (Mol. Plant, 2021)

Cytochrome P450 Protocols - Nelson, D. R. (Cytochrome P450 Nomenclature, 2004, 2006)

(untitled) - Meunier, B.; de Visser, S. P.; Shaik, S. (Chem. Rev., 2004)

(untitled) - Poulos, T. L. (Chem. Rev., 2014)

(untitled) - Guengerich, F. P. (ACS Catal., 2018)

(untitled) - Rittle, J.; Green, M. T. (Science, 2010)

(untitled) - Dubey, K. D.; Shaik, S. (Acc. Chem. Res., 2019)

(untitled) - Chen, C.-C.; Min, J.; Zhang, L.; Yang, Y.; Yu, X.; Guo, R.-T. (ChemBioChem, 2021)

Cytochrome P450: Structure, Mechanism, and Biochemistry - Ortiz de Montellano, P. R. (Substrate Oxidation by Cytochrome P450 Enzyme, 2015)

(untitled) - Bak, S.; Kahn, R. A.; Olsen, C. E.; Halkier, B. A. (Plant J., 1997)

(untitled) - Kushiro, M.; Nakano, T.; Sato, K.; Yamagishi, K.; Asami, T.; Nakano, A.; Takatsuto, S.; Fujioka, S.; Ebizuka, Y.; Yoshida, S. (Biochem. Biophys. Res. Commun., 2001)

(untitled) - Polturak, G.; Dippe, M.; Stephenson, M. J.; Chandra Misra, R.; Owen, C.; Ramirez-Gonzalez, R. H.; Haidoulis, J. F.; Schoonbeek, H.-J.; Chartrain, L.; Borrill, P.; Nelson, D. R.; Brown, J. K. M.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2022)

(untitled) - Field, B.; Fiston-Lavier, A.-S.; Kemen, A.; Geisler, K.; Quesneville, H.; Osbourn, A. E. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Castillo, D. A.; Kolesnikova, M. D.; Matsuda, S. P. T. (J. Am. Chem. Soc., 2013)

(untitled) - Hodgson, H.; De La Peña, R.; Stephenson, M. J.; Thimmappa, R.; Vincent, J. L.; Sattely, E. S.; Osbourn, A. (Proc. Natl. Acad. Sci. U. S. A., 2019)

(untitled) - Krokida, A.; Delis, C.; Geisler, K.; Garagounis, C.; Tsikou, D.; Peña‐Rodríguez, L. M.; Katsarou, D.; Field, B.; Osbourn, A. E.; Papadopoulou, K. K. (New Phytol., 2013)

(untitled) - Tsukagoshi, Y.; Ohyama, K.; Seki, H.; Akashi, T.; Muranaka, T.; Suzuki, H.; Fujimoto, Y. (Phytochemistry, 2016)

(untitled) - Takase, S.; Kera, K.; Nagashima, Y.; Mannen, K.; Hosouchi, T.; Shinpo, S.; Kawashima, M.; Kotake, Y.; Yamada, H.; Saga, Y.; Otaka, J.; Araya, H.; et al. (J. Biol. Chem., 2019)

(untitled) - Shang, Y.; Ma, Y.; Zhou, Y.; Zhang, H.; Duan, L.; Chen, H.; Zeng, J.; Zhou, Q.; Wang, S.; Gu, W.; Liu, M.; Ren, J.; et al. (Science, 2014)

(untitled) - Zhou, Y.; Ma, Y.; Zeng, J.; Duan, L.; Xue, X.; Wang, H.; Lin, T.; Liu, Z.; Zeng, K.; Zhong, Y.; Zhang, S.; Hu, Q.; et al. (Nat. Plants (London, U. K.), 2016)

(untitled) - Christ, B.; Xu, C.; Xu, M.; Li, F.-S.; Wada, N.; Mitchell, A. J.; Han, X.-L.; Wen, M.-L.; Fujita, M.; Weng, J.-K. (Nat. Commun., 2019)

(untitled) - Li, L.; Lin, S.; Chen, Y.; Wang, Y.; Xiao, L.; Ye, X.; Sun, L.; Zhan, R.; Xu, H. (Front. Plant Sci., 2022)

(untitled) - Shibuya, M.; Hoshino, M.; Katsube, Y.; Hayashi, H.; Kushiro, T.; Ebizuka, Y. (FEBS J., 2006)

(untitled) - Moses, T.; Pollier, J.; Almagro, L.; Buyst, D.; Van Montagu, M.; Pedreño, M. A.; Martins, J. C.; Thevelein, J. M.; Goossens, A. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Seki, H.; Ohyama, K.; Sawai, S.; Mizutani, M.; Ohnishi, T.; Sudo, H.; Akashi, T.; Aoki, T.; Saito, K.; Muranaka, T. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Moses, T.; Thevelein, J. M.; Goossens, A.; Pollier, J. (Phytochemistry, 2014)

(untitled) - Field, B.; Osbourn, A. E. (Science, 2008)

(untitled) - Hansen, N. L.; Miettinen, K.; Zhao, Y.; Ignea, C.; Andreadelli, A.; Raadam, M. H.; Makris, A. M.; Møller, B. L.; Stærk, D.; Bak, S.; Kampranis, S. C. (Microb. Cell Fact., 2020)

(untitled) - Bicalho, K. U.; Santoni, M. M.; Arendt, P.; Zanelli, C. F.; Furlan, M.; Goossens, A.; Pollier, J. (Plant Cell Physiol., 2019)

(untitled) - Fukushima, E. O.; Seki, H.; Sawai, S.; Suzuki, M.; Ohyama, K.; Saito, K.; Muranaka, T. (Plant Cell Physiol., 2013)

(untitled) - Fanani, M. Z.; Fukushima, E. O.; Sawai, S.; Tang, J.; Ishimori, M.; Sudo, H.; Ohyama, K.; Seki, H.; Saito, K.; Muranaka, T. (Front. Plant Sci., 2019)

(untitled) - Seki, H.; Sawai, S.; Ohyama, K.; Mizutani, M.; Ohnishi, T.; Sudo, H.; Fukushima, E. O.; Akashi, T.; Aoki, T.; Saito, K.; Muranaka, T. (Plant Cell, 2011)

(untitled) - Biazzi, E.; Carelli, M.; Tava, A.; Abbruscato, P.; Losini, I.; Avato, P.; Scotti, C.; Calderini, O. (Mol. Plant, 2015)

(untitled) - Tzin, V.; Snyder, J. H.; Yang, D. S.; Huhman, D. V.; Watson, B. S.; Allen, S. N.; Tang, Y.; Miettinen, K.; Arendt, P.; Pollier, J.; Goossens, A.; Sumner, L. W. (Metabolomics, 2019)

(untitled) - Yano, R.; Takagi, K.; Takada, Y.; Mukaiyama, K.; Tsukamoto, C.; Sayama, T.; Kaga, A.; Anai, T.; Sawai, S.; Ohyama, K.; Saito, K.; Ishimoto, M. (Plant J., 2017)

(untitled) - Han, J. Y.; Chun, J.-H.; Oh, S. A.; Park, S.-B.; Hwang, H.-S.; Lee, H.; Choi, Y. E. (Plant Cell Physiol., 2018)

(untitled) - Liu, Q.; Khakimov, B.; Cárdenas, P. D.; Cozzi, F.; Olsen, C. E.; Jensen, K. R.; Hauser, T. P.; Bak, S. (New Phytol., 2019)

(untitled) - Kim, O. T.; Um, Y.; Jin, M. L.; Kim, J. U.; Hegebarth, D.; Busta, L.; Racovita, R. C.; Jetter, R. (Plant Cell Physiol., 2018)

(untitled) - Ohnishi, T.; Nomura, T.; Watanabe, B.; Ohta, D.; Yokota, T.; Miyagawa, H.; Sakata, K.; Mizutani, M. (Phytochemistry, 2006)

(untitled) - Dai, Z.; Liu, Y.; Sun, Z.; Wang, D.; Qu, G.; Ma, X.; Fan, F.; Zhang, L.; Li, S.; Zhang, X. (Metab. Eng., 2019)

(untitled) - Shimada, Y.; Fujioka, S.; Miyauchi, N.; Kushiro, M.; Takatsuto, S.; Nomura, T.; Yokota, T.; Kamiya, Y.; Bishop, G. J.; Yoshida, S. (Plant Physiol., 2001)

(untitled) - Bishop, G. J.; Nomura, T.; Yokota, T.; Harrison, K.; Noguchi, T.; Fujioka, S.; Takatsuto, S.; Jones, J. D. G.; Kamiya, Y. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Shimada, Y.; Goda, H.; Nakamura, A.; Takatsuto, S.; Fujioka, S.; Yoshida, S. (Plant Physiol., 2003)

(untitled) - Nomura, T.; Kushiro, T.; Yokota, T.; Kamiya, Y.; Bishop, G. J.; Yamaguchi, S. (J. Biol. Chem., 2005)

(untitled) - Moses, T.; Pollier, J.; Faizal, A.; Apers, S.; Pieters, L.; Thevelein, J. M.; Geelen, D.; Goossens, A. (Mol. Plant, 2015)

(untitled) - Ohnishi, T.; Godza, B.; Watanabe, B.; Fujioka, S.; Hategan, L.; Ide, K.; Shibata, K.; Yokota, T.; Szekeres, M.; Mizutani, M. (J. Biol. Chem., 2012)

(untitled) - Fujita, S.; Ohnishi, T.; Watanabe, B.; Yokota, T.; Takatsuto, S.; Fujioka, S.; Yoshida, S.; Sakata, K.; Mizutani, M. (Plant J., 2006)

(untitled) - Sakamoto, T.; Morinaka, Y.; Ohnishi, T.; Sunohara, H.; Fujioka, S.; Ueguchi-Tanaka, M.; Mizutani, M.; Sakata, K.; Takatsuto, S.; Yoshida, S.; Tanaka, H.; Kitano, H.; et al. (Nat. Biotechnol., 2006)

(untitled) - Ohnishi, T.; Watanabe, B.; Sakata, K.; Mizutani, M. (Biosci., Biotechnol., Biochem., 2006)

(untitled) - Augustin, M. M.; Ruzicka, D. R.; Shukla, A. K.; Augustin, J. M.; Starks, C. M.; O'Neil‐Johnson, M.; McKain, M. R.; Evans, B. S.; Barrett, M. D.; Smithson, A.; Wong, G. K.-S.; Deyholos, M. K.; et al. (Plant J., 2015)

(untitled) - Yin, Y.; Gao, L.; Zhang, X.; Gao, W. (Phytochemistry, 2018)

(untitled) - Zhou, C.; Yang, Y.; Tian, J.; Wu, Y.; An, F.; Li, C.; Zhang, Y. (Plant J., 2022)

(untitled) - Ohnishi, T.; Szatmari, A.-M.; Watanabe, B.; Fujita, S.; Bancos, S.; Koncz, C.; Lafos, M.; Shibata, K.; Yokota, T.; Sakata, K.; Szekeres, M.; Mizutani, M. (Plant Cell, 2006)

(untitled) - Sakamoto, T.; Ohnishi, T.; Fujioka, S.; Watanabe, B.; Mizutani, M. (Plant Physiol. Biochem., 2012)

(untitled) - Dong, L.; Almeida, A.; Pollier, J.; Khakimov, B.; Bassard, J.-E.; Miettinen, K.; Stærk, D.; Mehran, R.; Olsen, C. E.; Motawia, M. S.; Goossens, A.; Bak, S. (Mol. Biol. Evol., 2021)

(untitled) - Yasumoto, S.; Fukushima, E. O.; Seki, H.; Muranaka, T. (FEBS Lett., 2016)

(untitled) - Carelli, M.; Biazzi, E.; Panara, F.; Tava, A.; Scaramelli, L.; Porceddu, A.; Graham, N.; Odoardi, M.; Piano, E.; Arcioni, S.; May, S.; Scotti, C.; et al. (Plant Cell, 2011)

(untitled) - Moses, T.; Pollier, J.; Shen, Q.; Soetaert, S.; Reed, J.; Erffelinck, M.-L.; Van Nieuwerburgh, F. C. W.; Vanden Bossche, R.; Osbourn, A.; Thevelein, J. M.; Deforce, D.; Tang, K.; et al. (Plant Cell, 2015)

(untitled) - Fukushima, E. O.; Seki, H.; Ohyama, K.; Ono, E.; Umemoto, N.; Mizutani, M.; Saito, K.; Muranaka, T. (Plant Cell Physiol., 2011)

(untitled) - Yasumoto, S.; Seki, H.; Shimizu, Y.; Fukushima, E. O.; Muranaka, T. (Front. Plant Sci., 2017)

(untitled) - Suzuki, H.; Fukushima, E. O.; Shimizu, Y.; Seki, H.; Fujisawa, Y.; Ishimoto, M.; Osakabe, K.; Osakabe, Y.; Muranaka, T. (Plant Cell Physiol., 2019)

(untitled) - Han, J.-Y.; Hwang, H.-S.; Choi, S.-W.; Kim, H.-J.; Choi, Y.-E. (Plant Cell Physiol., 2012)

(untitled) - Fiallos-Jurado, J.; Pollier, J.; Moses, T.; Arendt, P.; Barriga-Medina, N.; Morillo, E.; Arahana, V.; de Lourdes Torres, M.; Goossens, A.; Leon-Reyes, A. (Plant Sci., 2016)

(untitled) - Khakimov, B.; Kuzina, V.; Erthmann, P. Ø.; Fukushima, E. O.; Augustin, J. M.; Olsen, C. E.; Scholtalbers, J.; Volpin, H.; Andersen, S. B.; Hauser, T. P.; Muranaka, T.; Bak, S. (Plant J., 2015)

(untitled) - Miettinen, K.; Pollier, J.; Buyst, D.; Arendt, P.; Csuk, R.; Sommerwerk, S.; Moses, T.; Mertens, J.; Sonawane, P. D.; Pauwels, L.; Aharoni, A.; Martins, J.; et al. (Nat. Commun., 2017)

(untitled) - Tamura, K.; Teranishi, Y.; Ueda, S.; Suzuki, H.; Kawano, N.; Yoshimatsu, K.; Saito, K.; Kawahara, N.; Muranaka, T.; Seki, H. (Plant Cell Physiol., 2017)

(untitled) - Huang, L.; Li, J.; Ye, H.; Li, C.; Wang, H.; Liu, B.; Zhang, Y. (Planta, 2012)

(untitled) - Huang, J.; Zha, W.; An, T.; Dong, H.; Huang, Y.; Wang, D.; Yu, R.; Duan, L.; Zhang, X.; Peters, R. J.; Dai, Z.; Zi, J. (Appl. Microbiol. Biotechnol., 2019)

(untitled) - Andre, C. M.; Legay, S.; Deleruelle, A.; Nieuwenhuizen, N.; Punter, M.; Brendolise, C.; Cooney, J. M.; Lateur, M.; Hausman, J.-F.; Larondelle, Y.; Laing, W. A. (New Phytol., 2016)

(untitled) - Tamura, K.; Seki, H.; Suzuki, H.; Kojoma, M.; Saito, K.; Muranaka, T. (Plant Cell Rep., 2017)

(untitled) - Zhou, C.; Li, J.; Li, C.; Zhang, Y. (BMC Biotechnol., 2016)

(untitled) - Ji, X.; Lin, S.; Chen, Y.; Liu, J.; Yun, X.; Wang, T.; Qin, J.; Luo, C.; Wang, K.; Zhao, Z.; Zhan, R.; Xu, H. (Front. Plant Sci., 2020)

(untitled) - Jo, H.-J.; Han, J. Y.; Hwang, H.-S.; Choi, Y. E. (Phytochemistry, 2017)

(untitled) - Misra, R. C.; Sharma, S.; Sandeep; Garg, A.; Chanotiya, C. S.; Ghosh, S. (New Phytol., 2017)

(untitled) - Sandeep; Misra, R. C.; Chanotiya, C. S.; Mukhopadhyay, P.; Ghosh, S. (New Phytol., 2019)

(untitled) - Zhang, R.; Xia, X.; Lindsey, K.; da Rocha, P. S. C. F. (J. Plant Physiol., 2012)

(untitled) - Morikawa, T.; Mizutani, M.; Aoki, N.; Watanabe, B.; Saga, H.; Saito, S.; Oikawa, A.; Suzuki, H.; Sakurai, N.; Shibata, D.; Wadano, A.; Sakata, K.; et al. (Plant Cell, 2006)

(untitled) - Edgar, R. C. (Nucleic Acids Res., 2004)

(untitled) - Jacobowitz, J. R.; Weng, J.-K. (Annu. Rev. Plant Biol., 2020)

Engineering Natural Product Biosynthesis: Methods and Protocols - Chuang, L.; Franke, J. (Rapid Combinatorial Coexpression of Biosynthetic Genes by Transient Expression in the Plant Host Nicotiana Benthamiana, 2022)

(untitled) - Dang, T.-T. T.; Franke, J.; Carqueijeiro, I. S. T.; Langley, C.; Courdavault, V.; O’Connor, S. E. (Nat. Chem. Biol., 2018)

(untitled) - Nett, R. S.; Lau, W.; Sattely, E. S. (Nature, 2020)

(untitled) - Arnqvist, L.; Persson, M.; Jonsson, L.; Dutta, P. C.; Sitbon, F. (Planta, 2008)

(untitled) - Cabello-Hurtado, F.; Taton, M.; Forthoffer, N.; Kahn, R.; Bak, S.; Rahier, A.; Werck-Reichhart, D. (Eur. J. Biochem., 1999)

(untitled) - Geisler, K.; Hughes, R. K.; Sainsbury, F.; Lomonossoff, G. P.; Rejzek, M.; Fairhurst, S.; Olsen, C.-E.; Motawia, M. S.; Melton, R. E.; Hemmings, A. M.; Bak, S.; Osbourn, A. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Kasai, R.; Nie, R.-L.; Nashi, K.; Ohtani, K.; Zhou, J.; Tao, G.-D.; Tanaka, O. (Agric. Biol. Chem., 1989)

(untitled) - Zhang, J.; Dai, L.; Yang, J.; Liu, C.; Men, Y.; Zeng, Y.; Cai, Y.; Zhu, Y.; Sun, Y. (Plant Cell Physiol., 2016)

(untitled) - Itkin, M.; Davidovich-Rikanati, R.; Cohen, S.; Portnoy, V.; Doron-Faigenboim, A.; Oren, E.; Freilich, S.; Tzuri, G.; Baranes, N.; Shen, S.; Petreikov, M.; Sertchook, R.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Han, J.-Y.; Kim, H.-J.; Kwon, Y.-S.; Choi, Y.-E. (Plant Cell Physiol., 2011)

(untitled) - Li, L.-J.; Tan, W.-S.; Li, W.-J.; Zhu, Y.-B.; Cheng, Y.-S.; Ni, H. (Int. J. Mol. Sci., 2019)

(untitled) - Pandreka, A.; Chaya, P. S.; Kumar, A.; Aarthy, T.; Mulani, F. A.; Bhagyashree, D. D.; B, S. H.; Jennifer, C.; Ponnusamy, S.; Nagegowda, D.; Thulasiram, H. V. (Phytochemistry, 2021)

(untitled) - Lian, X.; Zhang, X.; Wang, F.; Wang, X.; Xue, Z.; Qi, X. (Physiol. Plant., 2020)

(untitled) - Chuang, L.; Liu, S.; Biedermann, D.; Franke, J. (Front. Plant Sci., 2022)

(untitled) - Jumper, J.; Evans, R.; Pritzel, A.; Green, T.; Figurnov, M.; Ronneberger, O.; Tunyasuvunakool, K.; Bates, R.; Žídek, A.; Potapenko, A.; Bridgland, A.; Meyer, C.; et al. (Nature, 2021)